Pengaruh Metode Eksperimen (Gejala Alam Banjir) terhadap Kemampuan Berpikir Kritis Anak di TK Aisyiyah Bebekan - Atikah Zahro; Gusmaniarti Gusmaniarti; Arafatun Ni'mah; Wardah Suweleh; Nur Afifah Ayu Winarsih; Nur Naura Nadhifa (Journal on Education, 2023)
Based on the results of field studies carried out through observation activities in learning at Aisyiyah Bebekan Kindergarten, it was found that there was a phenomenon of children's critical thinking abilities that were not optimal when learning in the room watching videos. children can’t focus when learning in the room. The percentage obtained between students who responded and those who responded less during reflection was 10% and 90%. In the observations we have observed, the method used is the experimental quantitative method. Therefore, it can be seen that using this experimental method greatly influences the effectiveness of learning, because it could be that when the video is broadcast, the class situation is less stable, so that the child's focus on learning is not focused on one object, in other words, the child's level of focus is less. The high knowledge of children is caused by the teacher using media in the learning process, namely audio-visual media (video). using non-experimental methods on natural phenomena it is known that the theme of flooding is the inability of children to mention the causes and effects of flooding by 71%.